Cognitive Abilities, Emotional Intelligence And Financial Decision Making: Mediation By Behavioral Biases - Muskaan Arora, Santha Kumari; Muskaan Arora, Santha Kumari (International Journal of Advanced Science and Technology, 2020)
Stock and risk preferences are the two most crucial aspects of personal financial decision making of the investors. Several studies have indicated that psychological attributes such as emotional intelligence and cognitive abilities affects the investors ' behavioral biases, stock preferences, and risk tolerance. However, researchers have not found any study exploring the underlying path through which cognitive and emotional intelligence is affecting investors' stock and risk preferences. Consequently, a mediational study was carried out to examine whether behavioral biases function as a connection between investors' psychological factors and their stock and risk preference.  A total of 396 males of northern part of India of the age of 25-40 years with education of graduation and above and their average monthly income was Rs. 25000-80000 volunteered to participate in the study. Loss aversion was assessed using an experiment on the task of lottery preference. The degree of regret was calculated by presenting the investor with a regretful circumstance, accompanied by a decision completing a regret scale. A self-designed questionnaire was used deduce the information about the investment of the subject in equities or stock and his risk preferences. The results of the research indicated that people with low cognitive and emotional intelligence prefer less stockholdings and fewer risks and in their financial decisions than people with high cognitive emotional intelligence. Moreover, behavioral bias such as regret was found to be mediator between the effect of cognitive and emotional intelligence on investors’ stock and risk preferences.